Glycemia and associated factors in a pediatric population in Mexico - Lares-Villaseñor, E.; Salazar-García, S.; Cossío-Torres, P. E.; Medina-Jasso, D. L.; Aradillas-García, C.; Portales-Pérez, D. P.; Vargas-Morales, J. M. (Frontiers in Pediatrics, 2023)
Aims In this study, we evaluated the association of sociodemographic, lifestyle and cardiometabolic factors with blood glucose levels in children and adolescents in Mexico. Methods An analytical cross-sectional study of 642 children and adolescents aged 6 to 19 years from different educational centers located in municipalities of the state of San Luis Potosí, Mexico, was carried out. Pearson χ2 and Spearman correlation tests and multiple linear regression models were used to evaluate the associations of the variables with glycemia. Results The prevalence of prediabetes was 8.0% in both sexes. Male participants were more likely to develop hyperglycemia than female participants (OR 2.7, 95% CI: 1.5-5.0). The variables associated with glucose levels were male sex, high socioeconomic status, inadequate diet, high blood pressure, and increased total cholesterol, LDL cholesterol, and triglycerides, which also explained up to 15.6% (p < 0.05) of the variability in glucose concentrations. Conclusion The detection of sociodemographic, lifestyle and cardiometabolic factors in children and adolescents will contribute to the implementation of prevention strategies for cardiometabolic diseases, among which prediabetes is common.